Blade depth - Kleshnev, V. (Rowing Biomechanics Newsletter, 2015)
Recently, some articles were published advocating deeper placement of the blade during the drive. The main argument for this was a higher blade efficiency due to less slippage, and at negligible extra drag on the shaft, because "the oar pivot (an imaginary stationary point - the centre of oar rotation) is located far inside from the blade, so the velocity of the shaft movement though the water is not high". Is this really true though?